(untitled) (The Research of Medical Science Review, 2025)
Objective: This study aimed to evaluate patients' satisfaction with the quality of nursing care and examine the association between patient characteristics and their level of satisfaction in public hospitals in Lahore, Pakistan. Design: A cross-sectional descriptive correlational design was adopted for this research. Methods: A convenience sampling technique was employed to recruit 1014 inpatients from six major hospitals in Lahore, including three public sector hospitals, two semi-private institutions, and one university-affiliated teaching hospital. Data collection was conducted from January 2025 to March 2025 using the Urdu-translated version of the Patient Satisfaction with Nursing Care Quality Questionnaire. Statistical analysis included Pearson correlation, independent t-tests, one-way ANOVA, and hierarchical multiple regression. Results: The study involved 1014 participants with a mean age of 51.3 years (SD = 18.6), with females representing 59.9% of the sample. Over two-thirds of respondents had some form of health insurance coverage, and 62.7% reported being unemployed. The average satisfaction score regarding nursing care quality was 68.2 (SD = 12.9), indicating a generally high level of satisfaction. Key factors significantly associated with higher satisfaction included higher household income (p < 0.001), higher educational attainment (p = 0.003), presence of health insurance (p < 0.001), admission to private or specialized units (p < 0.001), occupancy of single-bed rooms (p = 0.001), excellent self-rated health status (p < 0.001), and willingness to recommend the hospital to others (p < 0.001). Conclusions: Patients’ satisfaction with nursing care quality is significantly influenced by both individual and institutional characteristics. Hospital administrators should incorporate these findings into quality improvement strategies to enhance nursing care experiences and patient outcomes across public sector facilities in Pakistan.